Estudantes do ensino fundamental com indícios de altas habilidades/superdotação : interações e aprendizagens em uma oficina de tecnologia assistiva - Batista, Sebastião Luiz (2011)
We observed a group of 17 5th –9th grade students from elementary school with evidence of high skills / giftedness, from the Centre for the Development of Potential and Talent - CEDET in Vitória / ES, who were participants in a Workshop on Assistive Technology, established as a practical contribution to the teaching-learning of school theoretical contents, especially in mathematics, using computer resources. The methodology was of qualitative character with a predominance of the observation of the participant type. In 2010, the activities carried out in the extra-curricular shift were weekly, with four hours' duration. There were 31 meetings, registered in films, audio recordings and field journals. We analyzed the development and engagement of students and mediators involved in the project the group called Intelligent Traffic. Families, teachers and coordinators were heard in meetings or through reports and interviews. The progressive understanding of various concepts of an interdisciplinary nature involving, among other technologies, robotics education, was analyzed. Problematic situations, which were collectively and individually examined, emerged and were solved by the students with the help of mediators. The 28th meeting was to present the results to the community. Considerations on ways for the school to address activities with the group of adolescents were highlighted.